Orga-Dete: An Improved Lightweight Deep Learning Model for Lung Organoid Detection and Classification - Xuan Huang; Qin Gao; Hanwen Zhang; Fuhong Min; Dong Li; Gangyin Luo (Applied Sciences)
Lung organoids play a crucial role in modeling drug responses in pulmonary diseases. However, their morphological analysis remains hindered by manual detection inefficiencies and the high computational cost of existing algorithms. To overcome these challenges, this study proposes Orga-Dete—a lightweight, high-precision detection model based on YOLOv11n—which first employs data augmentation to mitigate the small-scale dataset and class imbalance issues, then optimizes via a triple co-optimization strategy: a bi-directional feature pyramid network for enhanced multi-scale feature fusion, MPCA for stronger micro-organoid feature response, and EMASlideLoss to address class imbalance. Validated on a lung organoid microscopy dataset, Orga-Dete achieves 81.4% mAP@0.5 with only 2.25 M parameters and 6.3 GFLOPs, surpassing the baseline model YOLOv11n by 3.5%. Ablation experiments confirm the synergistic effects of these modules in enhancing morphological feature extraction. With its balance of precision and efficiency, Orga-Dete offers a scalable solution for high-throughput organoid analysis, underscoring its potential for personalized medicine and drug screening.